2017
DOI: 10.1111/imb.12317
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid is hydroxylated by Laodelphax striatellus CYP6AY3v2

Abstract: Laodelphax striatellus (Fallén) is one of the most destructive pests of rice, and has developed high resistance to imidacloprid. Our previous work indicated a strong association between imidacloprid resistance and the overexpression of a cytochrome P450 gene CYP6AY3v2 in a L. striatellus imidacloprid resistant strain (Imid-R). In this study, a transgenic Drosophila melanogaster line that overexpressed the L. striatellus CYP6AY3v2 gene was established and was found to confer increased levels of imidacloprid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Similarly, overexpression of 12 P450 genes was observed in a laboratory‐selected imidacloprid‐resistant N. lugens strain, and CYP6AY1 , CYP6ER1 , CYP4CE1 and CYP6CW1 have been suggested to play important roles in imidacloprid resistance . The P450 genes associated with neonicotinoid resistance have also been reported in many other insects, such as CYP6AY3v2 and CYP353D1v2 in L. striatellus , CYP6G1 in D. melanogaster and CYP6CM1vQ in B. tabaci . Thus, it was reasonable to conclude that CYP15G1 , CYP6CS1 , CYP6CW1 , CYP6ER1 , CYP4C62 , CYP4DE1 , CYP417A1 and CYP419A1 were relevant for sulfoxaflor resistance in N. lugens .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, overexpression of 12 P450 genes was observed in a laboratory‐selected imidacloprid‐resistant N. lugens strain, and CYP6AY1 , CYP6ER1 , CYP4CE1 and CYP6CW1 have been suggested to play important roles in imidacloprid resistance . The P450 genes associated with neonicotinoid resistance have also been reported in many other insects, such as CYP6AY3v2 and CYP353D1v2 in L. striatellus , CYP6G1 in D. melanogaster and CYP6CM1vQ in B. tabaci . Thus, it was reasonable to conclude that CYP15G1 , CYP6CS1 , CYP6CW1 , CYP6ER1 , CYP4C62 , CYP4DE1 , CYP417A1 and CYP419A1 were relevant for sulfoxaflor resistance in N. lugens .…”
Section: Discussionmentioning
confidence: 73%
“…38 The P450 genes associated with neonicotinoid resistance have also been reported in many other insects, such as CYP6AY3v2 and CYP353D1v2 in L. striatellus, CYP6G1 in D. melanogaster and CYP6CM1vQ in B. tabaci. 37,[39][40][41] Thus, it was reasonable to conclude that CYP15G1, CYP6CS1, CYP6CW1, CYP6ER1, CYP4C62, CYP4DE1, CYP417A1 and CYP419A1 were relevant for sulfoxaflor resistance in N. lugens. In the current study, after RNAi depressed the expression level of CYP6ER1, which had shown the greatest increase in expression (36.87-fold), the susceptibility of SFX-SEL (G 39 ) individuals to sulfoxaflor significantly increased (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among the tested insecticides, CYP439A1v3 (Miah MA, unpublished) and CYP6FU1 were demonstrated to metabolize only deltamethrin. CYP6AY3v2 could hydrolyze only imidacloprid, 16 and CYP353D1v2 could metabolize both imidacloprid 17 and buprofezin. 18 None of the tested CYP genes could degrade chlorpyrifos.…”
Section: Discussionmentioning
confidence: 99%
“…The cytochrome P450 genes CYP353D1v2 , CYP6FU1 , CYP6AY3v2 , and CYP439A1v3 were previously reported to be overexpressed in a deltamethrin resistant strain in L. striatellus , which also showed cross‐resistance to imidacloprid and chlorpyrifos (Xu et al, ). Accordingly, these genes have been functionally expressed (Elzaki et al, ; R. Wang et al, ) and tested for their capability for the degradation of common insecticides. Among the overexpressed P450s (from the deltamethrin‐resistant strain of L. striatellus ), CYP353D1v2 , CYP6FU1 , and CYP6AY3v2 were already confirmed for their catalytical role to metabolize various insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…The first three P450s have been functionally expressed in vitro and tested for insecticide degradation. Among these three P450s, CYP353D1v2 was found capable of catalyzing the degradation of imidacloprid (Elzaki, Miah, Wu, et al, ) and buprofezin (Elzaki, Miah, & Han, ), whereas CYP6AY3v2 catalyzed imidacloprid degradation (R. Wang et al, ). Only CYP6FU1 was found capable of deltamethrin degradation (Elzaki, Miah, Peng, et al, ).…”
Section: Introductionmentioning
confidence: 99%